GEOENVIROMENTAL EFFECTS OF THE M=6.4 17 NOVEMBER 2015 EARTHQUAKE ON SOUTH LEFKADA, IONIAN SEA, GREECE - Papathanassiou, G.; Ganas, A.; Moshou, A.; Valkaniotis, S. (Bulletin of the Geological Society of Greece, 2016)
The 17th November Mw=6.4 shallow event occurred along a N20±5°E strike-slip fault with right-lateral sense of slip. The earthquake caused a lot of structural damage to the villages of Agios Petros, Athani, Dragano and Komilio, all located in south Lefkada island. Environmental effects include liquefaction, extensive rock falls and landslides. No surface ruptures were found in the field. Road cracks are interpreted as secondary phenomena of gravitational nature induced by ground shaking. The value of the macroseismic intensity ESI-07 was assessed as VIII-IX. The documentation of the earthquake-induced environmental effects was realized using the Earthquake Geo Survey App. (for Android OS).